An Analysis of the Determinants of Bank Stability in the Banking Industry of Nepal - Gwachha, Krishna Prasad (Khwopa Journal, 2023)
Bank stability refers to the ability of a financial institution to maintain consistent and secure operations, even in the face of economic challenges or shocks. This research study examines the determinants of bank stability in the Nepalese banking industry. The study analyzed data from commercial banks over a wide time range from 2001 to 2023, utilizing the autoregressive distributed lag (ARDL) model technique. The study found that bank size, funding risk, liquidity risk, and GDP growth have a positive and significant impact on bank stability in Nepal. The study also found that credit risk has a negative impact on bank stability. This implies that higher levels of credit risk increase the likelihood of bank instability in Nepal. Banks must give utmost priority to effectively managing and controlling bank size, funding risk, liquidity risk, and fostering GDP growth in order to bolster bank stability and fortify the country's financial system. However, the study also found that credit risk has a negative impact on bank stability. This implies that higher levels of credit risk increase the likelihood of bank instability in Nepal. The implications of the research study for policymakers, regulators, and banks, emphasize the need for effective risk management practices, adequate capitalization, diversified funding sources, and a supportive economic environment to ensure a stable banking sector. The implications of this finding hold great importance for policymakers, as they highlight the crucial role of preserving current bank stability in order to attain even greater stability in the future.